2020
DOI: 10.32479/ijeep.9023
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Carbon Dioxide Emissions: Evidence From Capital of Vietnam

Abstract: The purpose of this paper is to investigate the relationship between carbon dioxide (CO 2 ) emissions, foreign direct investment (FDI), income per capita and energy consumption (EC) in the capital of Vietnam from 1990 to 2015. The empirical results indicate that EC is a major contributor of environmental degradation while FDI marginally contribute to the current status. Moreover, a one-way causality is found to be running from carbon dioxide (CO 2 ) emissions, EC, FDI to income in the long-run. Then, the new e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
7
3
0
Order By: Relevance
“…The study by Lau et al [55] supported the evidence from Balibey [54] regarding a two-way causality between CO 2 emissions and FDI. The results of Lau et al [55] are similar to the findings of Minh [57] for Vietnam (1990Vietnam ( -2015, which, through ARDL models, concluded that the FDI contributes marginally to environmental degradation, in the short and long term. Nevertheless, they are contradictory to findings for Vietnam [57], with a similar methodology, Phuong and Tuyen [58] did not find statistically significant evidence to conclude that the FDI has an impact on environmental pollution.…”
Section: Brief Literature Reviewsupporting
confidence: 70%
See 1 more Smart Citation
“…The study by Lau et al [55] supported the evidence from Balibey [54] regarding a two-way causality between CO 2 emissions and FDI. The results of Lau et al [55] are similar to the findings of Minh [57] for Vietnam (1990Vietnam ( -2015, which, through ARDL models, concluded that the FDI contributes marginally to environmental degradation, in the short and long term. Nevertheless, they are contradictory to findings for Vietnam [57], with a similar methodology, Phuong and Tuyen [58] did not find statistically significant evidence to conclude that the FDI has an impact on environmental pollution.…”
Section: Brief Literature Reviewsupporting
confidence: 70%
“…The results of Lau et al [55] are similar to the findings of Minh [57] for Vietnam (1990Vietnam ( -2015, which, through ARDL models, concluded that the FDI contributes marginally to environmental degradation, in the short and long term. Nevertheless, they are contradictory to findings for Vietnam [57], with a similar methodology, Phuong and Tuyen [58] did not find statistically significant evidence to conclude that the FDI has an impact on environmental pollution. In a similar context, for Singapore, estimated long-term elasticities (through ARDL models) [59] showed that FDI inflows not only lead to higher economic growth, but also better environmental quality.…”
Section: Brief Literature Reviewsupporting
confidence: 70%
“…Some FDI inflows are linked to high polluting items that surge the emanation of CO 2 in host nations. This supports the pollution haven hypothesis (Minh, 2020). Exudations of CO 2 are also being abated by some FDI technologies concurring with the pollution hallo hypothesis (Sarkodie and Strezov).…”
Section: Model Specificationsupporting
confidence: 84%
“…On the OECD region, Ahmad et al (2020) carried out an investigative study and confirmed FDI as a vital promoter of CO 2 secretions. This finding supports that of Li et al (2020a) and Minh (2020) for Vietnam, but contradicts that of Huang et al (2019) for Chinese provinces. These conflicting revelations suggests that the debate on the connection between FDI and the emanation of CO 2 is far from over and demanded for further explorations like ours.…”
Section: Fdi-co 2 Emission Nexussupporting
confidence: 70%
See 1 more Smart Citation